Urinary tract infection in pregnant women: an integrative review (Research, Society and Development, 2021)
Urinary tract infections (UTI) are considered the most frequent clinical complication in pregnancy, it arises due to a failure in the defense system against installed agents that can cause injuries of varying degrees for both the mother and the fetus. The present study points out the main microbiological agents, clinical classifications, complications arising and therapeutic approaches. An integrative literature review was carried out, using articles published between 2016 and 2021, in Portuguese, English and Spanish, which were published in full in the PubMed, SciELO and LILACS databases. UTIs in pregnancy are caused by hormonal, anatomical and physiological factors, these conditions promote the bacterial growth of this pathology. These infections are usually caused by bacteria from the intestinal microbiota that contaminate the urinary tract, with Escherichia coli standing out most predominantly in 80% of cases. For an effective treatment it is necessary to determine the bacteria causing the infection, to select the appropriate antibiotic. Therefore, to reduce and control cases of tract infections, prenatal consultations and early examinations to diagnose the infection should be carried out in order to prevent possible perinatal and maternal complications.